EMOTION DETECTION AND RECOGNITION OF EMOJI AND TEXT USED IN CUSTOMERS’ FEEDBACK: STRATEGY VIA FACEBOOK ADVERTISING FOR MICRO BUSINESS - Jocelyn D. Magtubo (LP2M Universitas Bina Mandiri Gorontalo, 2022)
Several researchers have examined and explored the emotions of individuals with how they communicate through text, however, as years pass by, communication style changes, emojis have been adapted. Analysis of emotions through emojis still needs to be accomplished.. The study focused only on the selected micro-businesses in Balanga City, Bataan from the Facebook page: Balanga City Market Place (n = 357). Data were analyzed using descriptive statistics such as mean and percentage. This quantitative study adopts the principles of Paul Ekman’s six basic emotions which are happiness, sadness, anger, fear, disgust, and surprise. This research aimed to help micro-businesses in formulating a refined existing technique to promote their products effectively based on the emotions of their customers’ feedback that the researchers analyzed. It is determined that the emotions expressed by the customers through their feedback, with the use of text and emojis, may be exploited as a new approach for micro-businesses to promote their brand. Particularly, in online advertising and customer feedback marketing. These analyzed emotions of consumers' feedback may benefit microbusinesses in terms of customer satisfaction, promotion, brand image, and decision-making which they may utilize to optimize operations that address the concern of the customer by considering the conveyed emotion from their feedback.